Polymer-based advanced fuctional composites for optoelectronic and energy applications - Kundachira Subramani, Nithin, 1987-; Siddaramaiah, H.; Lee, Joong Hee (Elsevier, 2021)
Polymer-Based Advanced Functional Composites for Optoelectronic and Energy Applications explains how polymer-based smart composites and nanocomposites can be prepared and utilized for novel optical, sensor and energy-related applications. The book begins with an introductory section on the fundamentals of smart polymer composites, including structure-property relationships and conjugated polymers. Other sections examine optical applications, including the use of polymer-based smart composites for luminescent solar concentrators, electro-chromic applications, light conversion applications, ultraviolet shielding applications, LED encapsulation applications, sensor applications, including gas-sensing, strain sensing, robotics and tactile sensors, with final sections covering energy-related applications, including energy harvesting, conversion, storage, vibrational energy harvesting, and more. This is an essential guide for researchers, scientists and advanced students in smart polymers and materials, polymer science, composites, nanocomposites, electronics and materials science. It is also a valuable book for scientists, R & D professionals and engineers working with products that could utilize smart polymer composites.